Whispers of fortune - Connealy, Mary (Connealy, Mary. Golden state treasure, 2025)
"Brody MacKenzie arrives at an orphan school in search of his runaway brothers who possess an old journal leading to a lost treasure. Ellie Hart runs the ranch's orphan school, and together with Brody, they embark on a thrilling search, discovering love amidst family secrets and old adversaries"--